Strategi Penerapan Metode Brainstorming dalam Meningkatkan Kemampuan Menulis Siswa di MIS Maraqitta’limat Anyar - Nurmawaddah, Nurmawaddah; Fajriyah, Nurul; Wardani , Oktavia (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Writing ability is an important basic skill in learning, but there are still many students at MIS Maraqitta’limat Anyar who have difficulty in writing. This difficulty is caused by the lack of learning strategies that can stimulate students’ creativity and critical thinking. Therefore, this study aims to analyse the effectiveness of the brainstorming method in improving students’ writing skills. This study used the Classroom Action Research (PTK) method with two cycles, which involved observation, interviews, questionnaires, and formative tests. The results showed that the brainstorming method had a positive impact on students’ writing skills. In the first cycle, students were better able to generate ideas, although they still faced difficulties in composing structured writing. In the second cycle, there was a more significant improvement in students’ engagement and the quality of their writing. The success of this method was supported by the freedom of thought given to students, group discussions that improved communication skills, as well as a more systematic outline. However, there are obstacles such as students’ lack of confidence and difficulty in organising ideas. Therefore, teacher guidance and additional strategies are needed to optimise the application of this method